SYMBOLIC VIOLENCE AGAINST WOMEN IN SEPASANG MATA DINAYA YANG TERPENJARA SHORT STORY BY NI KOMANG ARIANI - Arianto, Tomi (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2018)
Sepasang Mata Dinaya yang Terpenjara short story expressed various problems related to the imbalance of social structure between women and men in Bali society. This is done in a structured and continuous to become a convention that is rooted down to the smallest social structure in society that is family. From the problems above, the research defined that the social problems present in those literary work included to the scope of sociological problems in literature work. The formulations of the problems in this research are as follows: 1) What is the scope of symbolic violence contained in Sepasang mata dinaya yang terpenjara? 2) How does the symbolic violence forms contained in a short story Sepasang mata dinaya yang terpenjara? To answer the research question, the researcher used literary theory related with the approach of sociology Pierre Bourdieu. The method used in this analysis is qualitative descriptive. The result of the analysis shows that the short story reveals various problems related to the inequality of social structure between women and men in Balinese society which has been formed in a structured and continuous culture that is rooted down to the smallest social structure in the family. From the dichotomy of these structures then arise forms of symbolic violence adopted from Bourdieu’s terminology. This form of symbolic violence is experienced in layers by agents who have more capital and dominate such as the parents of Dinaya, her husband, and the people who apply the patriarchal culture. This form of symbolic violence is reflected in: symbolic violence by parents (including Dinaya's mother) against her child (Dinaya). symbolic violence of an individual Man (Dinaya's husband) against his wife (Dinaya), and Symbolic Violence by Society (cultural norms) on Balinese women.